KONSEP PEDAGOGIK DALAM PEMIKIRAN IBNU SAHNUN DAN AL-QABISI - Saifullah Saifullah (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
Ibn al-Qabisi Sahnun and are two classical Islamic thinkers who are very concerned about education. Ibn Sahnun was popular earlier than al-Qabisi in the 3rd century of Islamic year, so that the world of Islamic education is heavily colored by the thoughts of the two figures. Ibn Sahnun is even known as the man who first sparked the concept of education that is independent from literary and philosophical schools of thought. The concept of education of Ibn Sahnun is oriented psychological conditions, for example in punishment. Meanwhile, al-Qabisi puts more focus on democratic educational system in the methods, curriculum or materials, procedures and other matters that are closely related to the concept of education in al-Kuttab at that time.